2004
DOI: 10.1093/protein/gzh027
|View full text |Cite
|
Sign up to set email alerts
|

Zinc binding drives the folding and association of the homo‐trimeric γ‐carbonic anhydrase from Methanosarcina thermophila

Abstract: Carbonic anhydrase from the archeon Methanosarcina thermophila (Cam) is a homo-trimeric enzyme, the left-handed beta-helical subunits of which bind three catalytic Zn(2+) ions at symmetry-related subunit interfaces. The observation of activity for holo-Cam at nanomolar concentrations provides a minimal estimated free energy of folding and assembly of the trimeric holo-complex of approximately 70 kcal (mol trimer)(-1) at standard state. Although the direct measurement of stability by chemical denaturation was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…These included the expected carbonic anhydrases/acetyltransferases/ isoleucine patch superfamily domain, PaaY/COG0663, and a single-stranded, left-hand beta-helix structure, cd00208. Comparative structural modeling of the N-terminal 200 amino acids of CcmM73 using a variety of homology and fold recognition programs such as 3D-PSSM/PHYRE (http://www.sbg.bio.ic.ac .uk/phyre/) (17) or Swiss Model (http://swissmodel.expasy.org //SWISS-MODEL.html) (36) also illustrated the potential of the N-terminal region of CcmM73 to form a left-hand betahelix structure that is characteristic of Cam (19,38) and other trimeric proteins (not shown). Structural and amino acid sequence comparisons indicated that all of the conserved Zncoordinating histidine residues and other residues identified as important for the binding of HCO 3 -and the formation of the Cam trimer are conserved in CcmM73 (41).…”
Section: Resultsmentioning
confidence: 99%
“…These included the expected carbonic anhydrases/acetyltransferases/ isoleucine patch superfamily domain, PaaY/COG0663, and a single-stranded, left-hand beta-helix structure, cd00208. Comparative structural modeling of the N-terminal 200 amino acids of CcmM73 using a variety of homology and fold recognition programs such as 3D-PSSM/PHYRE (http://www.sbg.bio.ic.ac .uk/phyre/) (17) or Swiss Model (http://swissmodel.expasy.org //SWISS-MODEL.html) (36) also illustrated the potential of the N-terminal region of CcmM73 to form a left-hand betahelix structure that is characteristic of Cam (19,38) and other trimeric proteins (not shown). Structural and amino acid sequence comparisons indicated that all of the conserved Zncoordinating histidine residues and other residues identified as important for the binding of HCO 3 -and the formation of the Cam trimer are conserved in CcmM73 (41).…”
Section: Resultsmentioning
confidence: 99%
“…Chemical denaturation has been used extensively to study the folding stability of both monomeric proteins and oligomers (22)(23)(24). However, beyond dimers, the mathematical formulation for data analysis becomes less trivial, and fewer systems have been investigated (25,26). Here, models describing two-state (monomer/ dimer) homodimerization, two-state (monomer/tetramer) homotetramerization, and three-state (monomer/dimer/tetramer) homotetramerization were developed (SI Appendix, Supplementary Methods), allowing equilibrium constants between the different oligomeric states to be obtained from the chemical denaturation data.…”
Section: Dependence Of the Ph-induced Coil-to-helix Transition On Promentioning
confidence: 99%
“…Rom et al (2006) also reported other zinc-binding phenomena relevance to ASR1-DNA interactions. The importance of zinc in mediating protein structure pertinent to its function has been further strengthened by studies on human prothymosin a, a protein characterized as natively unfolded (Uversky et al, 2000b) and also by zinc-driven folding and oligomerization of g-carbonic anhydrase (Simler et al, 2004). Folding of apo-metalloprotein has been reported to be induced by the binding of bivalent ions, including zinc (Ejnik et al, 2002), and the folding and stability of the nuclear hormone receptor DNAbinding domain was shown to be zinc dependent (Low et al, 2002).…”
Section: Zinc Binding and Desiccation Induce Order And Dimerization Imentioning
confidence: 99%